Sugar beet pectin–sodium caseinate conjugate stabilised emulsions: An investigation into the relationship between interfacial and bulk rheological properties for varying types of conjugates - Zhang, Juyang (2018)
There have been successful cases of conjugating polysaccharide and protein through electrostatic attraction, enzymatic cross-linking, and Maillard reaction in the literature. However, the effect of different interaction mechanisms on physiochemical properties of polysaccharide-protein conjugates under different environment stresses have not been clearly defined. The aim of this research was to test the hypothesis that the different interaction mechanisms of a mixed biopolymer system, designed to stabilise an oil-in-water emulsion have an impact upon the aggregation and rheological properties of this emulsion system at different environment stresses (pH and thermal treatment). The chosen mixed biopolymer system was sugar beet pectin (SBP) and sodium caseinate (SC) at mixing ratios of SBP:SC at 1:1, 1:3 and 3:1 respectively. Physical and chemical conjugates prepared by electrostatic complexation near the isoelectric point of SC, enzyme catalysed oxidation and Maillard reactions, respectively, were included. Emulsions were then processed, at pH 4.5, near the isoelectric point of SC via high shear overhead mixing followed by an assessment for stability against coalescence, zeta potential and dynamic rheological properties of the emulsion cream phase. All three types of SBP:SC conjugates stabilised the emulsion interfaces at an SBP:SC ratio of 1:1 at both pH 4.5 and pH 7, as did the 3:1 ratio of SBP:SC at pH 4.5, meaning that the emulsions were stable against coalescence. Extensive flocculation was observed for the 1:3 ratio of SBP:SC at pH 4.5. Moreover, heat treatment (80 ℃ for 10 minutes) had an effect on the aggregation properties of all three types of SBP:SC conjugates stabilised emulsion at both pH 4.5 and pH 7. Oscillatory rheological data were affected by the mixing ratio as well as by the type of conjugate. All emulsion cream phases and replicated droplet interfaces showed predominantly elastic behaviour, and also where one conjugate type showed higher shear storage modulus (G’) at pH 7, e.g. the enzyme-created conjugate at a mixing ratio of 1:1, compared to another one the trend was the same for dilatational interfacial storage modulus (E’). To include one observation here, the slope of G’ versus frequency assessed in the linear viscoelastic domain revealed the strongest gel-like behaviour for 1:3 ratio electrostatic and Maillard-based conjugates, compared to a slight increase in G’ versus frequency for all other systems. The research suggests that SBP ratios have a heavy impact on the aggregation properties of SBP-SC conjugates and conjugate-stabilised emulsions.